Fixation of Sacroiliac Fraktur-Luxation Using Plate 2.0 with screw 2.0 mm cortical self-tapping and 2.7 mm cortical non self-tapping - Erwin .; Rusli .; Amiruddin .; Teuku Fadrial Karmil; Muhammad Fauzih Asjikin; Afif Yuda Kusuma (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2022)
The Mixed Shih-Tzu dog, 3 years old and 4.3 kg body weight, had clinical signs of unable to stand, both rear limbs suffer from diplegic lameness so that they are only able to rely on both forelimbs. The owner said that her dog is traumatized by a four-wheeled vehicle. The results of blood profile before surgery showed physiological, only an increase in leukocyte cells 18.83 x103/µL. The radiographic examination with a ventral-dorsal position shows oblique fractures in the pelvic dexter and dislocation of the pelvic sacroiliac sinister bone. The method of handling used was open reduction internal fixation (ORIF) using a 2.0 veterinary cuttable plate (VCP) bone plate with a 2.0 mm cortical self-tapping screw for pelvic fractures and 2.7 mm cortical non-self-tapping for sacroiliac dislocations. The dog walked and showed a good progress in one week after ORIF, based on clinical and post-operative radiographic examinations, sacroiliac fracture-dislocation fixation using VCP with 2.0 mm self-tapping screw cortical for pelvic fracture and 2.7 mm non self-tapping for sacroiliac dislocation provides excellent stabilization and no visible complications.